(untitled) (Swiss Medical Weekly, 2012)
INTRODUCTION: Current fracture clinic models, especially with the advent of reductions in junior doctors’ hours, may limit outpatient trainee education and patient care. We have designed a new fracture clinic model, involving an initial consultant-led case review focused on patient management and trainee education. METHODS: Prospective outcomes for all new patients attending the redesigned fracture clinic over a 3-week period in 2010 (n = 240) were compared with a historical cohort from the same period in 2009 (n = 296). The primary outcome measure was the proportion of patients with direct consultant input. Secondary outcome measures included patient discharge rates, return rates, use of the nurse-led fracture clinic and the incidence of adverse event reporting. Trainees attending each clinic completed a five-point Likert questionnaire assessing the adequacy of education, support, staff morale and standards of patient care, before and after introduction of the clinic redesign. Using a separate Likert questionnaire, emergency room (ER) staff were evaluated to determine the impact of the new style clinic on their education, daily practice and interprofessional relations. Adverse events were gathered from the ‘incident record 1’ (IR1) reporting system. RESULTS: The percentage of cases given consultant input increased significantly from 33% in 2009 to 84% in 2010 (p <0.0001), while the proportion of patients requiring physical review by a consultant fell by 21% (p <0.0001). Return rates were reduced by 14% (p = 0.013) and use of the nurse-led fracture clinic improved by 10% (p = 0.0028). There was a median improvement in trainee perception of education from 2 (interquartile range 1.25–2.75) to 5 (4.25–5, p = 0.011), senior support from 2 (2–3) to 5 (4–5, p = 0.017) and patient care from 3 (3-4) to 5 (4–5, p = 0.015). ER staff found the new style clinic was educational, practice changing and improved interprofessional relations, but that it did not interfere with ER duties. The incidence of adverse incidents reported fell from 8 per year to 0 per year after the introduction of the new style clinic. CONCLUSIONS: Our model of fracture-clinic redesign has significantly enhanced consultant input into patient care without additional funding. In addition, we have demonstrated increased service efficiency and significant improvements in staff support, morale and education. In the face of current economic and training challenges, we recommend this new model as a tool that will enhance patient and trainee experience.